Hydrotalcite as an Efficient and Reusable Catalyst for Acylation of Phenols, Amines and Thiols Under Solvent-free Conditions - A. R. Massah; R. J. Kalbasi; M. Toghiani; B. Hojati; M. Adibnejad (E-Journal of Chemistry)
A wide variety of alcohols, phenols, amines and thiols were efficiently acylated with carboxylic acid anhydrides and chlorides in the presence of Hydrotalcite under solvent-free conditions at room temperature in good to high yields. Eco-friendly conditions and reusability of the catalyst are the most important advantages of this protocol.